SOSIALISASI SOLUSI ASAP DAPUR PINTAR UMKM KERUPUK PALEMBANG DAN PENGGUNAANNYA - Lindawati; Aryanti (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
UMKM (Micro, Small and Medium Enterprises) Kemplang cracker production by Hj. Eva Yunus is one of the kemplang cracker producers in Palembang. The process of frying kemplang crackers in the kitchen generates a lot of smoke, making the room dirty, smelly, and stuffy, and it also affects the air quality. The smoke produced during this process poses health risks. To tackle this issue, a smart exhaust fan using IoT-based fuzzy logic has been designed for the UMKM smart kitchen model. However, the owners and employees of this UMKM are not familiar with how to use this smart exhaust fan effectively. Educating and raising awareness about smart exhaust fans using IoT-based fuzzy logic is essential, as it is a crucial solution to mitigate smoke in the smart kitchen model of the UMKM, producing typical Palembang crackers.